Effect of MLC tracking latency on conformal volumetric modulated arc therapy (VMAT) plans in 4D stereotactic lung treatment - Bedford, James L. (Radiother Oncol, 2015)
BACKGROUND AND PURPOSE: The latency of a multileaf collimator (MLC) tracking system used to overcome respiratory motion causes misalignment of the treatment beam with respect to the gross tumour volume, which may result in reduced target coverage. This study investigates the magnitude of this effect. MATERIAL AND METHODS: Simulated superior–inferior breathing motion was used to construct histograms of isocentre offset with respect to the gross tumour volume (GTV) for a variety of tracking latencies. Dose distributions for conformal volumetric modulated arc therapy (VMAT) arcs were then calculated at a range of offsets and summed according to these displacement histograms. The results were verified by delivering the plans to a Delta(4) phantom on a motion platform. RESULTS: In the absence of an internal target margin, a tracking latency of 150 ms reduces the GTV D(95%) by approximately 2%. With a margin of 2 mm, the same drop in dose occurs for a tracking latency of 450 ms. Lung V(13Gy) is unaffected by a range of latencies. These results are supported by the phantom measurements. CONCLUSIONS: Assuming that internal motion can be modelled by a rigid translation of the patient, MLC tracking of conformal VMAT can be effectively accomplished in the absence of an internal target margin for substantial breathing motion (4 s period and 20 mm peak–peak amplitude) so long as the system latency is less than 150 ms.